Health care costs associated with Attention-Deficit/Hyperactivity Disorder in childhood: An Australian population based study - Lucas, Nina; Gold, Lisa; Sciberras, Emma; Hiscock, Harriet; Efron, Daryl; Nicholson, Jan (My University, 2013)
Background and aims: Despite the high prevalence of ADHD, the associated costs to the Australian health care system are unknown. Little is known about the age-related differences in health care costs for children with ADHD or the costs associated with persistent ADHD. We aimed to investigate: 1) the health care costs for children with and without ADHD diagnosis/clinical symptoms from 4-9 years; and 2) whether health care costs vary according to the persistence of ADHD symptoms. Method: Data were from waves 1-3 of the Longitudinal Study of Australian Children, in which 4,983 children were followed from 4-9 years of age. ADHD was defined by parent-reported ADHD diagnosis and/or clinically elevated Inattention-Hyperactivity scores on the Strengths and Difficulties Questionnaire (SDQ). Participant data was linked to reliable administrative data on health care costs from the Medicare Benefits Scheme (rebated health care attendances) and Pharmaceutical Benefits Scheme (medications). Adjusted analyses controlled for demographic factors and internalising/externalising comorbidities (SDQ emotional and conduct problems scales). Results: Costs associated with health care attendances (p≤.009) and medications (p≤.006) were significantly higher for children with ADHD at each age examined and particularly for those with persistent ADHD symptoms (p<.001). Excess population health care costs amounted to $24-29 million over 6 years, from 4-9 years of age. Conclusions: This study demonstrates that ADHD is associated with significant health care costs from early in life. In addition to improved outcomes for the child, early identification and intervention for ADHD has the potential to reap substantial health cost savings.
Keywords: Income & Finance -- Expenditure and constraints on expenditure; Health -- Medications; Child Development; Child Development -- Behaviour; Childhood and child development; Health and wellbeing; Income, wealth and finances; Health; Income & Finance; Child Development; Medications; Expenditure and constraints on expenditure; Behaviour; Income, wealth and finances; Childhood and child development; Health and wellbeing